2017
DOI: 10.1039/c6cy01980c
|View full text |Cite
|
Sign up to set email alerts
|

Z-scheme CdS–Au–BiVO4with enhanced photocatalytic activity for organic contaminant decomposition

Abstract: A Z-scheme heterogeneous photocatalyst CdS–Au–BiVO4was synthesized for the first time by photo-reduction and deposition–precipitation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…The compositions of various BiVO 4 ‐based samples were further confirmed by X‐ray photoelectron spectroscopy (XPS) analyses (Figure S3, Supporting Information). UV–vis absorption measurements (Figure S4, Supporting Information) showed that the similar visible‐light absorption of BiVO 4 {010}‐Au and BiVO 4 {110}–Au was broader relative to that of the pristine BiVO 4 crystal, which was ascribed to localized surface plasmon resonance absorption from the Au particles . Moreover, the absorption spectrum of BiVO 4 {010}–Cu 2 O improved after the deposition of Cu 2 O on the BiVO 4 surface, which was due to the characteristic absorption of Cu 2 O.…”
Section: Resultsmentioning
confidence: 98%
“…The compositions of various BiVO 4 ‐based samples were further confirmed by X‐ray photoelectron spectroscopy (XPS) analyses (Figure S3, Supporting Information). UV–vis absorption measurements (Figure S4, Supporting Information) showed that the similar visible‐light absorption of BiVO 4 {010}‐Au and BiVO 4 {110}–Au was broader relative to that of the pristine BiVO 4 crystal, which was ascribed to localized surface plasmon resonance absorption from the Au particles . Moreover, the absorption spectrum of BiVO 4 {010}–Cu 2 O improved after the deposition of Cu 2 O on the BiVO 4 surface, which was due to the characteristic absorption of Cu 2 O.…”
Section: Resultsmentioning
confidence: 98%
“…15,16 To date, many studies about Z-scheme heterojunction structures have been reported, such as g-C 3 N 4 /WO 3 , CdS/Au/TO 2 , CdS/ Au/WO 3 , Mn x Cd 1Àx S/WO 3 , ZnO/Au/SnO 2 , CeO 2 /Ag/AgBr, WO 3 /Au/ In 2 S 3 , CdS/Au/BiVO 4 and BiOI/Pt/g-C 3 N 4 . [17][18][19][20][21][22][23][24][25] In most cases of the Zscheme heterojunction catalytic system, however, noble metals are used as the electron mediator, such as Pt, Au and Ag, which can increase the cost of preparation and application. 26 Thus, it is necessary to construct direct Z-scheme heterojunction structures.…”
Section: Introductionmentioning
confidence: 99%
“…The two strong peaks at 164.03 eV and 158.73 eV with the orbital splitting of 5.3 eV, corresponding to Bi 4f 5/2 and Bi 4f 7/2 , are the characteristics of Bi 3+ species for the as‐prepared BiVO 4 film . The 1/2 and 3/2 spin‐orbit doublet components of the V 5+ of the same electrode are located at 523.7 eV and 516.25 eV, respectively (see Figure d) . After the deposition of Au nanoislands, the V 2p and Bi 4f peaks are slightly blue shifted (≈0.1 eV) compared with the bare BiVO 4 , suggesting an electron transfer from Au to BiVO 4 , which could be attributed to the relatively high electronegativity of Au (see Figure c,d) .…”
Section: Resultsmentioning
confidence: 94%